Influence of SnO2, MgO, and MnO3 nanoparticles on Some Physical Characteristics of PVP: CMC films (Journal of the College of Basic Education, 2024)
In this work, the physical properties of pure composite films “PVP:CMC” impregnated with nanoparticles “SnO2, MgO, and MnO3” were investigated. The solution casting method was used to make the films, The solution casting method is considered one of the simple and effective methods for preparing “PVP:CMC” . The material's transmittance and reflectivity were both found to be affected; it was discovered that the electrical conductivity of the produced membranes increases with rising frequency values and that the transmittance tends to decrease in the near-infrared regions. Combining these nanomaterials with "PVP:CMC" films was found to decrease the energy gap and increase the material's absorption in the visible and infrared spectrum. ultraviolet light. The obtained results show that the physical yield of “PVP:CMC” films is greatly affected by the merging of "SnO2, MgO, and MnO3" physical discrimination. This makes “PVP:CMC” films viable candidates for numerous applications, including certified sensors and biomedical sensors.